Feasibility Test Of A Gamification-Based Fashion Adventure Board Game As A Learning Media For Basic Fashion Design - Desi Fitrianita; Sri Endah Wahyuningsih (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
This study aims to develop and test the feasibility of a gamification-based Fashion Adventure board game for the Basic Fashion Design subject in the 2025/2026 academic year, targeting 10th-grade students at SMK Bina Nusantara Ungaran. This study employed a Research and Development (R&D) method with the ADDIE development model, which includes analysis, design, development, Implementation, and evaluation stages. The implementation and evaluation stages were not fully implemented because the research focused on testing the media's feasibility during the development stage. The research subjects consisted of media experts, material experts, and 10th-grade students, who served as respondents in the limited trial. Data collection techniques used validation questionnaires from media experts and material experts, as well as student response questionnaires. Data were analyzed using descriptive quantitative techniques by calculating the percentage of feasibility and user response. The results showed that the Fashion Adventure board game was categorized as very feasible based on the assessments of media experts and material experts. Furthermore, student responses were categorized as very good, indicating that the media was considered engaging, easy to use, and helpful in helping students understand the style and look of material in fashion design. Therefore, the Fashion Adventure board game is suitable for use as a learning support medium during the development stage. Keywords: board games, gamification, learning media, fashion design, SMK